Esophageal Plasmacytoma Diagnosed in a Patient Presenting with Cardiac Symptoms: A Novel Case. (10th September 2013) - Rimmer, Cheryl; Hazra, Anup; Gulli, Vito M.; Siderits, Richard; Castaldi, Mark; Zamir, Zafar
Abstract : Extramedullary plasmacytoma is the uncommon phenomenon of a plasma cell neoplasm occurring outside of the bone marrow. Primary plasmacytoma is a rare occurrence in the gastrointestinal tract and exceptional to originate in the esophagus. We present a novel case of a 62-year-old man who presented to our emergency department with chest pain. A cardiovascular workup was negative, and an endoscopy was subsequently performed. The endoscopy findings showed evidence of Grade IV esophagitis with ulcerations extending from 25 cm to 32 cm. Histopathological examination revealed marked acute and chronic inflammation, granulation tissue, and overlying necroinflammatory exudate. However, sheets of plasma cells, some with prominent nucleoli, were also seen. Immunohistochemically, the plasma cells expressed CD138 and MUM1 and were IgG kappa restricted. A bone marrow biopsy was performed which was negative for involvement. This is a novel case of esophageal plasmacytoma diagnosed on endoscopy in a patient presenting with acute chest pain.